Analysis of RNA Interference Targeted Against Human Antigen R (HuR) to Reduce Vascular Endothelial Growth Factor (VEGF) Protein Expression in Human Retinal Pigment Epithelial Cells - Supe, Shibani; Dighe, Vikas; Upadhya, Archana; Singh, Kavita (Molecular biotechnology, 2024)
VEGF-A or vascular endothelial growth factor-A is an important factor in enabling neovascularization and angiogenesis. VEGF-A is regulated transcriptionally as well as post transcriptionally. Human antigen R (HuR) belonging to the embryonic lethal abnormal vision (ELAV) family is a key regulator promoting stabilization of VEGF-A mRNA. In this research we investigate, whether HuR targeted RNA interference would enable the reduction of the VEGF-A protein in human retinal pigment epithelial cells (ARPE-19) in-vitro, in normoxic conditions. Three siRNA molecules with sequences complementary to three regions of the HuR mRNA were designed. The three designed siRNA molecules were individually transfected in ARPE-19 cells using Lipofectamine™2000 reagent. Post-transfection (24 h, 48 h, 72 h), downregulation of HuR mRNA was estimated by real-time polymerase reaction, while HuR protein and VEGF-A protein levels were semi-quantitatively determined by western blotting techniques. VEGF-A protein levels were additionally quantified using ELISA techniques. All experiments were done in triplicate. The designed siRNA could successfully downregulate HuR mRNA with concomitant decreases in HuR and VEGF-A protein. The study reveals that HuR downregulation can prominently downregulate VEGF-A, making the protein a target for therapy against pathological angiogenesis conditions such as diabetic retinopathy.